Design, fabrication and test of an embedded lightweight kinematic autopilot (ELKA). Issue 2 (6th May 2014) - Petricca, Luca; Hrishikeshavan, Vikram; Ohlckers, Per; Chopra, Inderjit
Abstract : Purpose: – Unmanned vehicles flight is controlled by embedded circuits in the aircraft, under the remote control of a pilot on the ground. This circuit, called autopilot, represents one of the key elements inside the vehicles. The authors developed one of the smallest autopilot, specifically designed for low-weight low-power applications. The paper aims to discuss these issues. Design/methodology/approach: – The system is based on STM32 ARM Cortex M3 microcontroller. It includes an onboard 9 DOF IMU (MPU9150) and a 2.4 GHz wireless transceiver (nRF24L01+). Findings: – The embedded lightweight kinematic autopilot (ELKA) can pilot up to eight servomotors, and can be used to monitor more than 100 sensors. The final assembled board is 28×21 mm2 and weighs around 1.2 grams (battery excluded), and has successfully passed initial functionality tests. Originality/value: – The authors presented the design, fabrication and initial tests of a lightweight kinematic autopilot (ELKA board version 1.0). The system has been designed in order to upgrade the state-of-art capability in sensing and processing over a previous autopilot (GINA), which is of similar weight and size. The small size (28×21 mm2) and the lightweight (around 1.2 grams) make ELKA one of the smallest autopilot in the world.